AKTUALISASI HUKUM KEWARISAN ISLAM (STUDI TENTANG KESADARAN HUKUM MASYARAKAT DI DESA WOLLANGI KECAMATAN BAREBBO TERHADAP HUKUM KEWARISAN ISLAM) - Asni Zubair (Al-Risalah: Jurnal Hukum Keluarga Islam (Ahwal Al-Syakhsiyah), 2021)
AbstractKnowledge society in the village of Wollangi sub-district of Barebbo about Islamic inheritance law is generally fixed on big gains the beneficiary children of men and women, namely in relation to one. The heirs of the boys gain a larger part than girls. Their knowledge such as this have been embedded in the community with the phrase majjujung makkunraie mallempa oroane. However, knowledge about things that should not be done in the Division of inheritance such as a ban on taking other people's rights, the prohibition of piling up treasures (estate only possessed by one of the heirs), not yet fully understood by the community. The attitude of the people in the village of Wollangi sub-district of Barebbo against the Islamic inheritance laws have mostly positive reaction especially from among the older generation. As for the youth generation less paying attention towards the Islamic inheritance laws which are considered complicated because they rarely get the Islamic inheritance laws about socialization. Awareness of Community law in the village of Wollangi sub-district of Barebbo to actualize the Islamic inheritance laws are quite adequate. But because of their knowledge and their understanding of Islamic inheritance law is still minimal cause them hampered in Islamic inheritance law is actualized.